2015
DOI: 10.1007/s00208-015-1302-0
|View full text |Cite
|
Sign up to set email alerts
|

On scalar curvature rigidity of vacuum static spaces

Abstract: Abstract. In this paper we extend the local scalar curvature rigidity result in [7] to a small domain on general vacuum static spaces, which confirms the interesting dichotomy of local surjectivity and local rigidity about the scalar curvature in general in the light of the paper [11]. We obtain the local scalar curvature rigidity of bounded domains in hyperbolic spaces. We also obtain the global scalar curvature rigidity for conformal deformations of metrics in the domains, where the lapse functions are posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
(80 reference statements)
0
25
0
Order By: Relevance
“…If κ = 0, V -static metrics reduce to vacuum static metrics. Under same assumptions on g, Qing and the author showed that g is isometric to ḡ (see [14]). This rigidity result suggests that the borderline case κ = 0 is not necessary to be considered.…”
Section: Introductionmentioning
confidence: 96%
“…If κ = 0, V -static metrics reduce to vacuum static metrics. Under same assumptions on g, Qing and the author showed that g is isometric to ḡ (see [14]). This rigidity result suggests that the borderline case κ = 0 is not necessary to be considered.…”
Section: Introductionmentioning
confidence: 96%
“…When restricted in conformal deformations, Qing and the author achieved a sharp rigidity result for vacuum static spaces with positive scalar curvature (c.f. [23]), which generalized Hang and Wang's work in [16] on upper hemisphere. On the other hand, motivated by a question proposed by Escobar ([14]), Barbosa, Mirandola and Vitorio found an elegant integral identity and with the aid of which they proved the rigidity part independently in a more general setting ( [2]).…”
Section: Introductionmentioning
confidence: 76%
“…Inspired by [5], Qing and the author generalized above rigidity result to generic vacuum static spaces ( [23]). This is in fact a sharp rigidity result due to Corvino's work on the stability of non-vacuum static domains ( [9]).…”
Section: Introductionmentioning
confidence: 99%
“…There are several motivations to consider the weighted curvature functional F given in item (d) of Proposition 2.2, which was first introduced by A. E. Fischer and J. E. Mardsen in [21]. Indeed, this functional plays a fundamental role in the theory of deformation and rigidity of static and V-static manifolds as we can observe in the works by S. Brendle et al [12], S. Brendle and F. C. Marques [11], G. Cox, P. Miao and L.-F. Tam [15] and J. Qing and W. Yuan [39]. Proof.…”
Section: Properties and Computationsmentioning
confidence: 89%